Self-knowledge in schizophrenia: importance, characteristics, and treatment - Harvey, Phillip D. (Henry Stewart Talks, 2025)
Schizophrenia symptom domains, Momentary cognitive self-assessment, Objective and subjective data, Meta cognitive Wisconsin Card Sorting Test (WCST), Performance and judgments: schizophrenia and bipolar disorder, iTEST